2020
DOI: 10.1101/2020.06.11.146894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying likely transmission pairs with pathogen sequence data using Kolmogorov Forward Equations; an application toM.bovisin cattle and badgers

Abstract: 18Established methods for whole-genome-sequencing (WGS) technology allow for the detection of 19 single-nucleotide polymorphisms (SNPs) in the pathogen genomes sourced from host samples. The 20 information obtained can be used to track the pathogen's evolution in time and potentially identify 21 'who-infected-whom' with unprecedented accuracy. Successful methods include 'phylodynamic 22 bovine/zoonotic tuberculosis, bTB) infection. 31Our results show that, even with such limited data and low diversity, the com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The pairwise transmission probability was calculated using the Kolmogorov Forward Equations (KFEs) [41], and the pairwise transmission probability matrix was reported in Figure 4. The KFEs methodology was used to calculate the probability of observing a pair of bTB infected hosts given their sampling time and the genetic divergence between their bacterial isolates, assuming that a direct transmission occurred between the pair.…”
Section: Pairwise Transmission Probability and Most Likely Transmissimentioning
confidence: 99%
See 4 more Smart Citations
“…The pairwise transmission probability was calculated using the Kolmogorov Forward Equations (KFEs) [41], and the pairwise transmission probability matrix was reported in Figure 4. The KFEs methodology was used to calculate the probability of observing a pair of bTB infected hosts given their sampling time and the genetic divergence between their bacterial isolates, assuming that a direct transmission occurred between the pair.…”
Section: Pairwise Transmission Probability and Most Likely Transmissimentioning
confidence: 99%
“…Results showed that random trees had a median [95 th quantile] of 17 [13][14][15][16][17][18][19][20][21] cattle-to-cattle, 26 [21][22][23][24][25][26][27][28][29][30][31] badger-to-badger, 14 [10][11][12][13][14][15][16][17][18][19] cattle-to-badger, and 6[2-10] badger-to-cattle transmissions ( Figure S4.3). We computed the most likely transmission tree by selecting the transmissions with highest probability within the sampled animals while avoiding loops in the tree (see [41]). The best tree ( Figure 4) showed that most of the transmissions in this system likely happened within-species, i.e.…”
Section: Pairwise Transmission Probability and Most Likely Transmissimentioning
confidence: 99%
See 3 more Smart Citations